Pengembangan Bahan Ajar Berbasis Pembelajaran Berdiferensiasi Materi Operasi Perkalian dan Pembagian Bilangan Cacah Kelas III A MI Terpadu Berkah - Muhammad Syabrina; Nur Husna Aulia; Nurlaili Jannah Ciptaningtyas; Milia Milia (JURNAL ILMIAH NUSANTARA, 2026)
Abstract. This study aims to develop teaching materials based on differentiated learning for third-grade students of MI Terpadu Berkah Palangka Raya City and determine its effectiveness through direct trials in the classroom. The research method used is research and development (R&D) with a field trial stage. The research subjects were fourth-grade students. Data collection techniques were carried out through observation, questionnaires, and documentation. The results of the questionnaire from material experts, design and field trials showed that this interactive learning media was very appropriate, with a percentage score of 100% including the qualification of "Very Appropriate" according to 99% design experts, teacher assessment of 100%, field trial results 72.20%, T-Test results 0.01 that the teaching materials were very significant in improving learning outcomes, and N-gain Analysis of 0.58 with moderate criteria. While the effectiveness of the teaching materials was 58.38 with a category that was quite effective for use in learning. The results of the study showed that the developed teaching materials were able to increase student activity and understanding in learning. Therefore, teaching materials based on differentiated learning are declared suitable for use in the learning process in elementary schools. Keywords: Development; Teaching Materials; Effectiveness; Learning; Outcomes; R&D. Abstrak. Penelitian ini bertujuan untuk mengembangkan bahan ajar berbasis pembelajaran berdiferensiasi pada siswa kelas III A MI Terpadu Berkah Kota Palangka Raya serta mengetahui efektivitasnya melalui uji coba langsung di kelas. Metode penelitian yang digunakan adalah penelitian dan pengembangan (Research and Development/R&D) dengan tahap uji coba lapangan. Subjek penelitian adalah siswa kelas III. Teknik pengumpulan data dilakukan melalui observasi, angket, dan dokumentasi. Hasil angket dari ahli materi, desain dan uji coba lapangan memperlihatkan bahwa media pembelajaran interaktif ini sangat sesuai, dengan score persentase 100% termasuk kualifikasi “Sangat Layak”menurut ahli desain 99%, penilaian guru sebesar 100%, Hasil uji coba lapangan 72,20%, hasil Uji T 0,01 bahwa bahan ajar sangat signifikan dalam meningkatkan hasil belajar, dan Analisis N-gain sebesar 0,58 dengan kriteria sedang. Sedangkan efektifitas dari bahan ajar adalah 58,38 dengan kategoro cukup efektif di gunakan dalam pembelajaran. Hasil penelitian menunjukkan bahwa bahan ajar yang dikembangkan mampu meningkatkan keaktifan dan pemahaman siswa dalam pembelajaran. Oleh karena itu, bahan ajar berbasis pembelajaran berdiferensiasi dinyatakan layak digunakan dalam proses pembelajaran di sekolah dasar. Kata kunci: Pengembangan; Bahan Ajar; Pembelajaran Berdiferensiasi; Efektifitas; Hasil Belajar; R&D.